2020
DOI: 10.1002/hep.31256
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular Vesicles Carrying Sphingolipid Cargo for the Diagnosis and Dynamic Risk Profiling of Alcoholic Hepatitis

Abstract: Background and Aims Alcoholic hepatitis (AH) is diagnosed by clinical criteria, although several objective scores facilitate risk stratification. Extracellular vesicles (EVs) have emerged as biomarkers for many diseases and are also implicated in the pathogenesis of AH. Therefore, we investigated whether plasma EV concentration and sphingolipid cargo could serve as diagnostic biomarkers for AH and inform prognosis to permit dynamic risk profiling of AH subjects. Approach and Results EVs were isolated and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 50 publications
(74 reference statements)
1
49
0
Order By: Relevance
“…Cells were cultured in an EV free 10% FBS medium. EVs were then isolated from cultured cells or human plasma samples as described earlier (Sehrawat et al, 2020a). Supernatants from cultured cells were subjected to differential ultracentrifugation for 45 mins (20,000 g) and twice for 2 hrs (110,000 g) at 4 • C. Determination of EV concentration and size was completed using nanoparticle tracking analysis (NTA) (NS300, Malvern Instruments, Malvern, United Kingdom).…”
Section: Isolation Of Extracellular Vesiclesmentioning
confidence: 99%
“…Cells were cultured in an EV free 10% FBS medium. EVs were then isolated from cultured cells or human plasma samples as described earlier (Sehrawat et al, 2020a). Supernatants from cultured cells were subjected to differential ultracentrifugation for 45 mins (20,000 g) and twice for 2 hrs (110,000 g) at 4 • C. Determination of EV concentration and size was completed using nanoparticle tracking analysis (NTA) (NS300, Malvern Instruments, Malvern, United Kingdom).…”
Section: Isolation Of Extracellular Vesiclesmentioning
confidence: 99%
“…Additionally, a very recent study showed that circulating EVs carrying a sphingolipid cargo might be helpful for the diagnosis of AH, and may allow dynamic risk profiling of these patients. [98]. Most recently, EVs have been used as a surrogate marker of improvement in clinical trials of patients with AH [99].…”
Section: Evs In Aldmentioning
confidence: 99%
“…Exosomes can also be used for prognostic analyses. Circulating EV concentrations and sphingolipid carrier characteristics can be used not only for the diagnosis and differentiation of AH, decompensated alcoholic cirrhosis, and other end-stage liver diseases but also for the prediction of the 90-day survival time ( 101 ).…”
Section: Exosome Roles In Prognosis and Treatmentmentioning
confidence: 99%